Difference between Pb and Cd Accumulation in 19 Elite Maize Inbred Lines and Application Prospects. (14th May 2012) - Zhang, Zhiming; Jin, Feng; Wang, Cui; Luo, Jun; Lin, Haijian; Xiang, Kui; Liu, Li; Zhao, Maojun; Zhang, Yunsong; Ding, Haiping; Zhou, Shufeng; Shen, Yaou; et al.
Abstract : In the last two decades, the accumulation of heavy metal in crop grains has become the study hotspot. In this study, 19 representative elite maize inbred lines and 3 hybrid varieties were investigated at the seedling stage, which can accumulate Pb and Cd in the stems and leaves, respectively. The results demonstrated that significant differences are among inbred lines for accumulation of heavy metals, implying that the Cd accumulation is significant correlation between the male parents and their hybrids and some inbred lines have been selected for cross-breeding with low Pb or Cd accumulation, such as S37, 9782, and ES40; Moreover, some inbred lines could be suitable for phytoremediation species for soil bioremediation with high levels of Pb and Cd accumulation, including 178, R08, 48-2, and Mo17ht.